KARAKTER TOKOH DALAM NOVEL LENTERA SENJA KARYA ALFIA RAMADHANI - Sri Sakinah Ulfa; La Yani Konisi; La Ode Syukur (Jurnal Bastra (Bahasa dan Sastra), 2026)
This research aims to describe the character traits in the novel Lentera Senja by Alfia Ramadhani. This study is categorized as library research using a descriptive qualitative method. The primary data source is the novel Lentera Senja, second edition, published in 2023 by Loveable Publisher in Jakarta, with a total of 280 pages. The research focuses on analyzing the characters’ traits through reading and note-taking techniques. The data were analyzed using an objective approach, describing the findings systematically and accurately based on the textual evidence. The term "descriptive" refers to the process of portraying the data as it is, while "qualitative" indicates the interpretation of interrelated conceptual understandings, delivered verbally and supported by relevant theories. The study highlights several key characters and their traits: Zayyan (responsibility, care, trustworthiness, respect, citizenship awareness, and fairness), Athar (care, fairness, responsibility, and trustworthiness), Khanza (care), Syafiya (care, responsibility, and respect), Zana (care), Haura (responsibility and fairness), Farzan (care), and Rizal (responsibility, care, and trustworthiness).